A negative liquid crystal compound and its application
By developing new liquid crystal compounds with high negative dielectric anisotropy and low rotational viscosity, the problem of slow response speed and high driving voltage of LCD monitors is solved, and faster response and lower voltage requirements are achieved, suitable for a variety of applications Display mode.
Patent Information
- Application Number
- CN202211696363.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-12-28
AI Technical Summary
The existing liquid crystal materials have problems such as slow response speed and high driving voltage in liquid crystal displays, which are difficult to meet the ever-increasing display technical requirements.
A new negative liquid crystal compound has been developed, with high negative dielectric anisotropy, good liquid crystal mutual solubility and relatively low rotational viscosity, through specific synthesis routes, such as metallization reaction of organolithium reagents, Suzuki reaction, trifluoro Boron ether, triethylsilane reaction, etc., prepare liquid crystal compounds with excellent structure.
It effectively reduces the driving voltage of the LCD display, improves the response speed, and maintains moderate optical anisotropy performance. It is suitable for a variety of liquid crystal display modes such as TN, ADS, VA, PSVA, FFS, IPS, etc.
Smart Images

Figure CN115806466B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of liquid crystal compounds, in particular to a novel negative liquid crystal compound and also to applications thereof. Background Art
[0002] The application of liquid crystal materials in the fields of information display materials, organic optoelectronic materials, etc. has great research value and bright application prospects. As a new type of display material, liquid crystal materials have many advantages, such as extremely low power consumption and low driving voltage. Compared with other materials, they also have the advantages of small size, light weight, long life, large display information volume, and no electromagnetic radiation. They can almost meet the requirements of various information displays, especially suitable for TFT-LCD (thin film transistor technology) products.
[0003] In the TFT active matrix system, there are TN (Twisted Nematic) mode, IPS (In-Plane Switching) mode, FFS (Fringe Field Switching) mode and VA (Vertical Alignment) mode. At present, TFT-LCD product technology has matured and successfully solved technical problems such as viewing angle, resolution, color saturation and brightness. Large-size and medium-sized TFT-LCD displays have gradually occupied the mainstream position of flat panel displays in their respective fields. At the same time, the requirements for display technology have been constantly improving, such as requiring liquid crystal displays to achieve faster response and reduce driving voltage to reduce power consumption.
[0004] Liquid crystal materials themselves play an important role in improving the performance of liquid crystal displays. In particular, it has been found that the performance of liquid crystal displays can be improved by reducing the rotational viscosity of liquid crystal materials and increasing the dielectric anisotropy △ε of liquid crystal materials. Therefore, in order to improve the performance of liquid crystal materials to adapt to new requirements, the synthesis of liquid crystal compounds with new structures and the study of structure-performance relationships have become an important task in the field of liquid crystals. Summary of the invention
[0005] The purpose of the present invention is to provide a new type of liquid crystal compound with negative dielectric anisotropy, which has the advantages of high negative dielectric anisotropy, good liquid crystal miscibility, relatively low rotational viscosity, etc., which are exactly what is needed to improve liquid crystal materials and have important application value.
[0006] In a first aspect, the present invention provides a negative liquid crystal compound, wherein the negative liquid crystal compound comprises a structure represented by general formula (I):
[0007]
[0008] in:
[0009] R1 and R2 each independently represent an alkyl group, an alkenyl group, an alkoxy group, a cycloalkyl group or a cycloalkoxy group having 1 to 12 carbon atoms;
[0010] Ring A represents 1,4-phenylene, 1,4-cyclohexylene, or 1,4-phenylene in which 1 to 4 hydrogen atoms are substituted by fluorine atoms;
[0011] Ring B represents 1,4-phenylene, 1,4-cyclohexylene, 1,4-cyclohexenylene, or 1,4-phenylene in which 1 to 4 hydrogen atoms are substituted by fluorine atoms;
[0012] m and n independently represent 0, 1 or 2;
[0013] Z1 and Z2 each independently represent a single bond, a double bond, an oxygen atom, -CH2CH2-, -CH2O-, -OCH2- or -CH=CH-.
[0014] As a preferred embodiment of the present invention, in the general formula (I), R1 and R2 each independently represent an alkyl or alkoxy group having 1 to 7 carbon atoms;
[0015] Ring A represents 1,4-phenylene, 1,4-cyclohexylene, or 1,4-phenylene in which 1 to 2 hydrogen atoms are substituted by fluorine atoms;
[0016] Ring B represents 1,4-phenylene, 1,4-cyclohexylene, 1,4-cyclohexenylene, or 1,4-phenylene in which 1 to 2 hydrogen atoms are substituted by fluorine atoms;
[0017] m and n independently represent 0 or 1;
[0018] Z1 and Z2 each independently represent a single bond or -CH2O-.
[0019] As a further preferred embodiment of the present invention, the negative liquid crystal compound comprises a structure shown in any one of Formulas I-1 to I-26:
[0020]
[0021]
[0022] In the above-mentioned general formulae I-1 to I-26, R1 and R2 each independently represent an alkyl group or an alkoxy group having 1 to 7 carbon atoms.
[0023] Preferably, in the above general formulae I-1 to I-26, R1 and R2 each independently represent an alkyl group having 2 to 5 carbon atoms.
[0024] As a further preferred embodiment of the present invention, the negative liquid crystal compound is selected from one or more of the following structures:
[0025]
[0026]
[0027]
[0028]
[0029]
[0030]
[0031]
[0032]
[0033]
[0034]
[0035]
[0036]
[0037]
[0038]
[0039] In a second aspect, the present invention provides a method for preparing the negative liquid crystal compound, which is specifically as follows.
[0040] In the first case, when ring B is 1,4-phenylene or 1,4-phenylene in which the hydrogen atom is replaced by a fluorine atom, and Z2 is a single bond, the synthetic route used for the synthesis of the liquid crystal compound is:
[0041]
[0042]
[0043] The synthesis method comprises the following steps:
[0044] (1) Metalation reaction with organolithium reagent, followed by reaction with borate ester, yields
[0045] (2) and Prepared by Suzuki reaction
[0046] In the step (1), The molar ratio of the organic lithium reagent to the borate ester is 1:(1.0-2.0):(1.0-3.0), and the reaction temperature is -50--100°C;
[0047] Wherein, the organic lithium reagent is selected from one or more of sec-butyl lithium, tert-butyl lithium or n-butyl lithium, and the borate ester is selected from one or more of trimethyl borate, triisopropyl borate, tributyl borate or triisobutyl borate.
[0048] In the step (2), and The molar ratio of feed is 1:(0.9-1.5), and the reaction temperature is 60-140°C.
[0049] In the second case, when ring B is 1,4-cyclohexylene and Z2 is a single bond, the synthesis route used for the synthesis of the liquid crystal compound is:
[0050]
[0051] The synthesis method comprises the following steps:
[0052] (1) Metalation reaction with organolithium reagents, followed by Reaction, get
[0053] (2) By reacting with boron trifluoride etherate and triethylsilane,
[0054] In the step (1), Organolithium reagents and The molar ratio of the feed is (1.0-3.0): (1.0-3.0): 1, and the reaction temperature is -50--100°C;
[0055] Wherein, the organic lithium reagent is selected from one or more of sec-butyl lithium, tert-butyl lithium or n-butyl lithium, preferably n-butyl lithium.
[0056] In the step (2), The molar ratio of boron trifluoride etherate to triethylsilane is 1:(1.0-3.0):(1.0-3.0), and the reaction temperature is -20 to -100°C.
[0057] In the third case, when ring B is 1,4-cyclohexenylene and Z2 is a single bond, the synthesis route used for the synthesis of the liquid crystal compound is:
[0058]
[0059] The synthesis method comprises the following steps:
[0060] (1) Metalation reaction with organolithium reagents, followed by Reaction, get
[0061] (2) Dehydration under acid catalysis gives
[0062] In the step (1), Organolithium reagents and The molar ratio of the feed is (1.0-3.0): (1.0-3.0): 1, and the reaction temperature is -50--100°C;
[0063] Wherein, the organic lithium reagent is selected from one or more of sec-butyl lithium, tert-butyl lithium or n-butyl lithium, preferably n-butyl lithium.
[0064] In the step (2), The molar ratio of the feed to the acid is 1:(0.02-0.2), and the reaction temperature is 50-130°C;
[0065] Wherein, the acid is selected from one or more of hydrochloric acid, sulfuric acid, formic acid, acetic acid, p-toluenesulfonic acid, and potassium hydrogen sulfate, preferably p-toluenesulfonic acid.
[0066] In the fourth case, when Z2 is -CH2O-, the synthesis route adopted for the synthesis of the liquid crystal compound is:
[0067]
[0068] The synthesis method comprises the following steps:
[0069] (1) Oxidation reaction to obtain
[0070] (2) and Through the Mitsunobu reaction, we can obtain
[0071] In the step (1), The molar ratio of the feed to the oxidant is 1:(1.0-3.0), and the reaction temperature is 20--100°C;
[0072] Wherein, the oxidant is selected from one or more of hydrogen peroxide, peracetic acid or perbenzoic acid, preferably hydrogen peroxide.
[0073] In the step (2), The molar ratio of phosphonium salt to azodicarboxylic acid is 1:(0.9-1.2):(1-3):(1-2), and the reaction temperature is 0-60°C;
[0074] Wherein, the phosphine salt is selected from one of triphenylphosphine and tri-tert-butylphosphine or a mixture of the two; the azodicarboxylic acid is selected from one of DIAD and DEAD or a mixture of the two.
[0075] The method described in the present invention may involve conventional post-treatment when necessary, and the conventional post-treatment may specifically include: extraction with dichloromethane, ethyl acetate or toluene, separation, water washing, drying, evaporation with a vacuum rotary evaporator, and purification of the obtained product by reduced pressure distillation or recrystallization and / or chromatographic separation.
[0076] In the above preparation methods, the definitions of the substituents involved are the same as described above.
[0077] In the above four synthesis schemes, the raw materials used The synthetic route is as follows:
[0078]
[0079] The specific synthesis includes the following steps:
[0080] (1) Metalation reaction with organolithium reagents, in the presence of cuprous iodide Reaction, get
[0081] (2) Reaction with bromoalkyl triphenylphosphine salt wittig gives
[0082] (3) Hydrogenation reaction
[0083] (4) Alkaline hydrolysis
[0084] (5) Reaction with thionyl chloride to obtain
[0085] (6) Friedel-Crafts acylation catalyzed by Lewis acid affords
[0086] (7) Reduction reaction with trifluoroacetic acid and triethylsilane gave
[0087] Wherein, R in the compounds involved in the above steps is the alkyl, alkenyl, alkoxy, cycloalkyl or cycloalkoxy group in which R2 in the obtained liquid crystal compound product has one less carbon element.
[0088] In step (1) of the above method, Organolithium reagents, cuprous iodide and The molar ratio of the feed is 1:(1.0-2.0):(1.0-2.0):(1.0-2.0), and the reaction temperature is -60 to -90°C; wherein the organic lithium reagent is selected from one or more of lithium dimethylamide, lithium amide or lithium diisopropylamine, preferably lithium diisopropylamine (LDA);
[0089] In the step (2), The molar ratio of the organic base to the bromoalkyl triphenylphosphine salt is 1:(1.0-2.0):(1.0-2.0), the reaction temperature is -20-20°C, and the organic base is selected from potassium tert-butyl alcoholate, sodium tert-butyl alcoholate or a mixture of the two.
[0090] In the step (3), The hydrogenation reaction temperature is 10-60°C, wherein the catalyst is one or a mixture of palladium carbon, ruthenium carbon, and Raney nickel, and the catalyst addition ratio is 0.5-20%;
[0091] In the step (4), The molar ratio of the alkali to the alkali is 1:(1.0-2.0), the reaction temperature is 50-100° C., and the alkali is selected from potassium hydroxide, sodium hydroxide, lithium hydroxide, or a mixture of two thereof.
[0092] In the step (5), The molar ratio of thionyl chloride to thionyl chloride is 1:(1-5), and the reaction temperature is 60-100°C;
[0093] In the step (6), The molar ratio of the Lewis acid to the raw material is 1: (1.0-2.0), and the reaction temperature is 30--20°C; wherein the Lewis acid is selected from one or more of aluminum trichloride, boron trifluoride or titanium tetrachloride, preferably aluminum trichloride;
[0094] In the step (7), The molar ratio of the reactants with trifluoroacetic acid and triethylsilane is 1:(1.0-4.0):(1.0-4.0), and the reaction temperature is 20-40°C.
[0095] The above preparation method can stably and efficiently obtain the liquid crystal compound of the present invention.
[0096] In a third aspect, the present invention provides a liquid crystal material composition, wherein the liquid crystal material composition comprises the negative liquid crystal compound described in the present invention.
[0097] Preferably, the mass percentage of the negative liquid crystal compound in the composition is 0.1 to 60%, more preferably 1 to 50%, and even more preferably 3 to 30%.
[0098] In a fourth aspect, the present invention provides an application of the negative liquid crystal compound or the liquid crystal material composition described in the present invention in the field of liquid phase display.
[0099] As a preferred embodiment, the present invention provides use of the negative liquid crystal compound or the liquid crystal material composition described in the present invention in a liquid display device.
[0100] Further preferably, the liquid crystal display device includes but is not limited to TN, ADS, VA, PSVA, FFS or IPS mode liquid crystal displays.
[0101] The present invention provides a new type of negative liquid crystal compound, which has high negative dielectric anisotropy, good liquid crystal mutual solubility, relatively low rotational viscosity, etc., which are just what is needed to improve liquid crystal materials and have important application value.
[0102] The liquid crystal compound provided by the present invention or the liquid crystal composition containing the liquid crystal compound provided by the present invention has extremely high negative dielectric anisotropy and low rotational viscosity, thereby effectively reducing the driving voltage of the liquid crystal display device and improving the response speed of the liquid crystal display device. At the same time, it has the advantages of moderate optical anisotropy value and high charge retention rate. It is a liquid crystal material with excellent performance and can be applied to liquid crystal display devices such as TN, ADS, VA, PSVA, FFS, IPS mode liquid crystal displays, etc. DETAILED DESCRIPTION
[0103] The technical scheme of the present invention is described in detail below. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0104] Unless otherwise specified, the raw materials can be obtained from public commercial channels.
[0105] Example 1
[0106] The structural formula of the liquid crystal compound prepared in this embodiment is:
[0107]
[0108] The synthesis route is as follows:
[0109]
[0110] The specific steps are as follows:
[0111] (1) Synthesis of compound LC-01-1
[0112] Add 114g o-difluorobenzene (1.0mol), 111g diisopropylamine (1.1mol), 700ml tetrahydrofuran into a three-necked flask, stir and cool to -70~-75℃, control the temperature and add 1.2mol n-butyl lithium dropwise, and react for 2h. Control the temperature at -70~-75℃ and slowly add 190g cuprous iodide (1.0mol) and react for 1h. Control the temperature at -70~-75℃ and add 165g ethyl chloroformyl acetate (1.1mol) dropwise, and react for 2h, then stir naturally overnight. Add 1000ml of 2M hydrochloric acid aqueous solution for acidification, and perform conventional post-treatment, GC: 75%, spin dry to obtain 256g, distill under reduced pressure, take the middle fraction GC: 98%, 165g, theoretical yield: 228g, yield: 72%;
[0113] (2) Synthesis of compound LC-01-2
[0114] Add 286g of ethyltriphenylphosphonium bromide (0.77mol) and 900ml of tetrahydrofuran to a three-necked flask, cool to -10~-15℃, add 94g of potassium tert-butyl alcohol (0.84mol) in batches, and react at -5~-10℃ for 2h. Slowly drop a mixed solution of 160g LC-01-1 (0.70mol) and 200ml of tetrahydrofuran at -5~-10℃, and react at -5~-10℃ for 2h. Add 100g of water to the reaction solution to terminate the reaction. Perform conventional post-treatment, and recrystallize from petroleum ether to obtain 151g of light yellow solid (compound LC-01-2, 0.63mol), GC: 99.6%, yield 90.0%;
[0115] (3) Synthesis of compound LC-01-3
[0116] Add 151g LC-01-2 (0.0.63mol), 300ml toluene, 100ml ethanol, 7.5g palladium carbon (water content 50%) into the hydrogenation kettle, and react at 30-40℃ for 5h. Sample test shows no olefin, and the palladium carbon is filtered. After desolventization, recrystallization from petroleum ether gives 143g of a light yellow solid (compound LC-01-3, 0.59mol), GC: 99.9%, yield 94.0%;
[0117] (4) Synthesis of Compound LC-01-4
[0118] 143g LC-01-3 (0.59mol), 35g sodium hydroxide (0.89mol), and 400ml ethanol were added to a three-necked flask, and then the temperature was slowly raised to 65-68°C, and refluxed for 4h. After the ethanol was distilled off, the reaction solution was poured into a beaker containing 100ml hydrochloric acid (PH<7), and conventional post-treatment was performed. Petroleum ether was passed through a column for desolventizing to obtain 120g of a light yellow solid (compound LC-01-4, 0.56mol), LC: 99.5%, yield 95.0%;
[0119] (5) Synthesis of Compound LC-01-5
[0120] Add 120g LC-01-4 (0.56mol) and 150g thionyl chloride (1.26mol) into a three-necked flask, heat to 70°C with stirring, and react for 5h. Perform conventional post-treatment to obtain 130g of light yellow liquid (compound LC-01-5, 0.56mol), with a yield of 100%;
[0121] (6) Synthesis of Compound LC-01-6
[0122] Add 112g aluminum chloride (0.84mol) and 300ml dichloromethane to a three-necked flask, cool to 0~-10℃, and add a mixed solution of 130g LC-01-5 (0.56mol) and 400ml dichloromethane dropwise under temperature control. After the addition, control the temperature at 0~-10℃ and stir for 2h, then heat to 30℃ and stir for 3h. Pour the reaction solution into ice water containing 260ml hydrochloric acid for acidification, and perform conventional post-treatment to obtain 93g of crude product (compound LC-01-6, 0.48mol), theoretical yield: 110g, GC: 99%, yield: 85%;
[0123] (7) Synthesis of Compound LC-01-7
[0124] Add 80.4g LC-01-6 (0.41mol) into a three-necked flask, add 96g triethylsilane (0.82mol) and 140g trifluoroacetic acid (1.23mol) at a temperature below 40°C, and stir at a temperature of 20°C for 4h. Pour the reaction solution into a mixed solution of 370g sodium carbonate (2.46mol) and 500ml water (PH>7), perform conventional post-treatment, and spin dry to obtain a crude product of 52.2g compound LC-01-7 (0.287mol), GC: 99%, theoretical yield: 74.6g, yield 70%;
[0125] (8) Synthesis of Compound LC-01-8
[0126] Under nitrogen protection, add 52.2g LC-01-7 (0.287mol) and 150ml tetrahydrofuran to the reaction bottle, control the temperature at -70~-80℃, add 0.37mol n-butyl lithium in n-hexane solution, keep warm for 1 hour, control the temperature at -60~-70℃, add 46.6g trimethyl borate (0.44mol), and then naturally return to -30℃. Add 400ml 2M hydrochloric acid aqueous solution for acidification, perform conventional post-treatment, and recrystallize from petroleum ether to obtain 59.7g of light yellow solid (compound LC-01-8, 0.264mol), HPLC: 99.6%, yield 92%;
[0127] (9) Synthesis of Compound LC-01
[0128] Under nitrogen protection, add 59.7g of compound LC-01-8 (0.264mol), 52.3g of compound 4-propylbromobenzene (0.264mol), 200ml N,N-dimethylformamide, 100ml deionized water, 72.8g of anhydrous potassium carbonate (0.53mol), 0.5g of tetrakistriphenylphosphine palladium to the reaction bottle, heat to 70°C and react for 3 hours. Perform conventional post-treatment, chromatographic purification, elution with n-hexane, and recrystallization from ethanol to obtain 63.4g of white solid (compound LC-01, 0.211mol), GC: 99.9%, yield: 80%.
[0129] The obtained white solid LC-01 was analyzed by GC-MS, and the m / z of the product was 300 (M+);
[0130] 1 H-NMR (300MHz, CDCl3): 0.82-2.90 (m, 17H), 7.10-7.60 (m, 5H).
[0131] Example 2
[0132] The structural formula of the liquid crystal compound prepared in this embodiment is:
[0133]
[0134] The synthesis route is as follows:
[0135]
[0136] The specific steps are as follows:
[0137] (1) Synthesis of compound LC-02-1
[0138] Under nitrogen protection, add 80g LC-01-7 (0.44mol) and 250ml tetrahydrofuran to the reaction bottle, control the temperature at -75~-85℃, add 0.48mol n-butyl lithium in n-hexane solution, keep warm for 1 hour, control the temperature at -75~-85℃, add 81.4g propyl dicyclohexyl ketone (0.37mol) and 100ml tetrahydrofuran solution, and then naturally return to -30℃. Add 300ml water to quench the reaction, perform conventional post-treatment, and obtain 121.2g of light yellow solid (compound LC-02-1, 0.3mol), GC: 99%, yield 81%;
[0139] (2) Synthesis of compound LC-02
[0140] Add 121.2g LC-02-1 (0.3mol), 5.6g p-toluenesulfonic acid (0.03mol), 0.1g 2,6-di-tert-butyl-p-cresol and 200ml toluene to the reaction bottle, reflux and separate the water for 8 hours. Perform conventional post-treatment to obtain 98.4g of white solid (compound LC-02, 0.255mol), GC: 99.9%, yield 85%.
[0141] The obtained white solid LC-02 was analyzed by GC-MS, and the m / z of the product was 386 (M+);
[0142] 1 H-NMR (300MHz, CDCl3): 0.88-2.88(m,34H), 5.62-5.80(m,1H), 6.80-7.00(m,1H).
[0143] Example 3
[0144] The structural formula of the liquid crystal compound prepared in this embodiment is:
[0145]
[0146] The synthesis route is as follows:
[0147]
[0148] The specific steps are as follows:
[0149] (1) Synthesis of compound LC-03
[0150] Under nitrogen protection, add 72.7g of compound LC-02-1 (0.18mol) and 150ml of dichloromethane to the reaction bottle, control the temperature at -70 to -80°C, add 41.8g of triethylsilane (0.36mol), keep the temperature for 0.5 hours, control the temperature at -70 to -80°C, add 56.2g of boron trifluoride etherate (0.39mol), and then naturally return to -10°C. Add 300ml of water to quench the reaction, and perform conventional post-treatment to obtain 52.5g of white solid (compound LC-03, 0.14mol), GC: 99.9%, yield 78%.
[0151] The obtained white solid LC-03 was analyzed by GC-MS, and the m / z of the product was 388 (M+);
[0152] 1 H-NMR (300MHz, CDCl3): 0.88-2.88 (m, 39H), 6.80-7.00 (m, 1H).
[0153] Example 4
[0154] The structural formula of the liquid crystal compound prepared in this embodiment is:
[0155]
[0156] The synthesis route is as follows:
[0157]
[0158] The specific steps are as follows:
[0159] (1) Synthesis of compound LC-04-1
[0160] Add 67.8g LC-01-8 (0.3mol) and 300ml dichloromethane to the reaction bottle, add 30% hydrogen peroxide (0.45mol) dropwise at 20-30°C, and reflux for 5 hours. Perform conventional post-treatment to obtain 53.4g of white solid (compound LC-04-1, 0.27mol), GC: 99.9%, yield 90%;
[0161] (2) Synthesis of compound LC-04
[0162] Add 53.4g LC-04-1 (0.27mol), 71.4 trans-propyl dicyclohexylmethanol (0.3mol), 288g triphenylphosphine (0.33mol), 800ml DMF to the reaction bottle, add 72.7g diisopropyl azodicarboxylate (0.36mol) dropwise at 10-20℃, and react at 30-40℃ for 4 hours. Perform conventional post-treatment to obtain 106.6g of white solid (compound LC-04, 0.225mol), GC: 99.9%, yield 83%;
[0163] The obtained white solid LC-04 was analyzed by GC-MS, and the m / z of the product was 418 (M+);
[0164] 1 H-NMR (300MHz, CDCl3): 0.88-2.88(m,37H), 4.00-4.50(m,2H), 6.80-7.00(m,1H).
[0165] The above preparation process may involve conventional post-treatment when necessary, such as extraction with dichloromethane, ethyl acetate or toluene, separation, washing with water, drying, evaporation with a vacuum rotary evaporator, and purification of the obtained product by reduced pressure distillation or recrystallization and / or chromatography.
[0166] With reference to the synthesis schemes of Examples 1-4 above, other specific liquid crystal compounds of the present invention can be synthesized by simply replacing the corresponding raw materials without changing any substantial operations.
[0167] The performance tests of the liquid crystal compounds prepared in Examples 1 to 4 of the present invention were carried out, as described below. According to conventional detection methods in the art, various performance parameters of the liquid crystal compounds were obtained by linear fitting, wherein the specific meanings of the various performance parameters are as follows:
[0168] Cp represents the clearing point of the liquid crystal (°C);
[0169] △n represents optical anisotropy (25°C);
[0170] △ε represents dielectric anisotropy (25°C, 1000Hz);
[0171] γ1 represents the rotational viscosity (mPa.s, 25°C).
[0172] Experimental Example 1
[0173] The performance parameter data of the compound LC-01 prepared in Example 1 and the liquid crystal compound of Comparative Example 1 were compared and sorted, and the test results are shown in Table 1:
[0174] Table 1: Performance test results of liquid crystal compounds
[0175]
[0176] It can be clearly seen from the test results in Table 1 that the liquid crystal compound provided by the present invention has higher negative dielectric anisotropy, moderate rotational viscosity γ1, good low-temperature miscibility and higher clearing point performance compared with traditional negative dielectric anisotropy compounds with similar chemical structures, which are exactly what is needed to improve liquid crystal materials and can effectively improve the dielectric anisotropy Δε of the liquid crystal composition, reduce the driving voltage, and obtain a liquid crystal composition with a faster response speed.
[0177] Experimental Example 2
[0178] The performance parameter data of the compound LC-02 prepared in Example 2 and the liquid crystal compound of Comparative Example 2 were compared and sorted out, and the test results are shown in Table 2:
[0179] Table 2: Performance test results of liquid crystal compounds
[0180]
[0181] It can be clearly seen from the test results in Table 2 that the liquid crystal compound provided by the present invention has higher negative dielectric anisotropy, moderate rotational viscosity γ1, good low-temperature miscibility and higher clearing point performance compared with traditional negative dielectric anisotropy compounds of similar chemical structures, which are exactly what is needed to improve liquid crystal materials and can effectively improve the dielectric anisotropy Δε of the liquid crystal composition, reduce the driving voltage, and obtain a liquid crystal composition with a faster response speed.
[0182] Experimental Example 3
[0183] The performance parameter data of the compound LC-03 prepared in Example 3 and the liquid crystal compound of Comparative Example 3 were compared and sorted out, and the test results are shown in Table 3:
[0184] Table 3: Performance test results of liquid crystal compounds
[0185]
[0186] It can be clearly seen from the test results in Table 3 that the liquid crystal compound provided by the present invention has higher negative dielectric anisotropy, moderate rotational viscosity γ1, good low-temperature miscibility and higher clearing point performance compared with traditional negative dielectric anisotropy compounds with similar chemical structures, which are exactly what is needed to improve liquid crystal materials and can effectively improve the dielectric anisotropy △ε of the liquid crystal composition, reduce the driving voltage, and obtain a liquid crystal composition with a faster response speed.
[0187] Experimental Example 4
[0188] The performance parameter data of the compound LC-04 prepared in Example 4 and the liquid crystal compound of Comparative Example 4 were compared and sorted out, and the test results are shown in Table 4:
[0189] Table 4: Performance test results of liquid crystal compounds
[0190]
[0191]
[0192] It can be clearly seen from the test results in Table 4 that the liquid crystal compound provided by the present invention has higher negative dielectric anisotropy, moderate rotational viscosity γ1, good low-temperature miscibility and higher clearing point performance compared with traditional negative dielectric anisotropy compounds of similar chemical structures, which are exactly what is needed to improve liquid crystal materials and can effectively improve the dielectric anisotropy Δε of the liquid crystal composition, reduce the driving voltage, and obtain a liquid crystal composition with a faster response speed.
[0193] In addition, after the liquid crystal compound provided by the present invention is specifically applied to a liquid crystal composition of a conventional system, it is found that it can improve the dielectric anisotropy △ε of the liquid crystal composition while maintaining a low rotational viscosity γ1 and an appropriate refractive index anisotropy △n. The resulting liquid crystal composition has significant fast response characteristics and low voltage driving characteristics.
[0194] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A negative liquid crystal compound, characterized in that: The negative liquid crystal compound is selected from one or more of the following structures:
2. A method for preparing the negative liquid crystal compound according to claim 1, characterized in that: The synthesis route adopted for the synthesis of the negative liquid crystal compound is: The synthesis method comprises the following steps: (1) Oxidation reaction to obtain (2) and Through the Mitsunobu reaction, we can obtain Ring A represents 1,4-cyclohexylene; Ring B represents 1,4-cyclohexylene; m and n represent 1 independently of each other; Z1 represents a single bond, R1 and R2 are as defined in claim 1.
3. A liquid crystal material composition, characterized in that: The liquid crystal material composition comprises the negative liquid crystal compound according to claim 1; the mass percentage of the negative liquid crystal compound in the composition is 0.1 to 60%.
4. The liquid crystal material composition according to claim 3, characterized in that: The mass percentage of the negative liquid crystal compound in the composition is 1 to 50%.
5. The liquid crystal material composition according to claim 4, characterized in that: The mass percentage of the negative liquid crystal compound in the composition is 3-30%.
6. Use of the negative liquid crystal compound according to claim 1 or the liquid crystal material composition according to any one of claims 3 to 5 in the field of liquid phase display.
7. The use according to claim 6, characterized in that: Application of the negative liquid crystal compound or the liquid crystal material composition in a liquid crystal display device.
8. The use according to claim 6, characterized in that: Application of the negative liquid crystal compound or the liquid crystal material composition in TN, ADS, VA, PSVA, FFS or IPS mode liquid crystal displays.
